Great Speeches by American Women - Edited by Daley, James (Mineola, New York Dover Publications, 2008)
From civil rights to the right to vote, women have spoken out with great power and eloquence throughout the annals of American history. Here are 21 legendary speeches from the country's most inspirational female voices, including Sojourner Truth, Susan B. Anthony, Eleanor Roosevelt, Hillary Rodham Clinton, Nancy Pelosi, and many others.
Keywords: Speeches, addresses, etc., American--Women authors